POLA PENGASUHAN SANTRI PESANTREN DARUL MUTTAQIN PARUNG BOGOR - Achmad Dudin Dasir; Munawiroh Munawiroh (Penamas, 2020)
Abstract This paper is the result of the author's research in 2019. The background of this study is the actual issue of the strategic patterns of parenting of students to be considered. The purpose of this study is to determine the pattern of parenting of students in the Darul Muttaqin boarding school in Bogor. Data and information obtained through this qualitative research are the result of the thoughts of caregivers, religious teachers, managers, experts and related officials as well as an analysis of parenting patterns of students in Darul Muttaqin Islamic boarding school in Bogor. From the results of this study several things are suggested, namely: Islamic boarding schools need to optimize the implementation of the guidance and supervision of students continuously so as to create a child-friendly boarding school; pesantren need to create awareness of students to obey, obey the rules and discipline that apply; boarding schools need to intensively establish cooperation between teachers, parents and related parties in overseeing the development of student learning and the existence in boarding schools; and people who entrust their children's education in pesantren should be able to trust and be more confident in the pesantren's parenting patterns.